Human Serum Albumin and Human Serum Albumin Nanoparticles as Carriers of 10-(2′-Pyrimidyl)-3,6-diazaphenothiazine: In Vitro Spectroscopic Studies - Aleksandra Owczarzy; Karolina Kulig; Beata Morak-Młodawska; Małgorzata Jeleń; Tammam Muhammetoglu; Wojciech Rogóż; Małgorzata Maciążek-Jurczyk (Molecules)
Human serum albumin (HSA) plays a fundamental role in the human body, including the transport of exogenous and endogenous substances. HSA is also a biopolymer with a great medical and pharmaceutical potential. Due to nontoxicity and biocompatibility, this protein can be used as a nanocarrier. 10-(2′-Pyrimidyl)-3,6-diazaphenothiazine (10-Pyr-3,6-DAPT) is a phenothiazine showing high anticancer potential in vitro against glioma, melanoma and breast cancer cells. Additionally, this compound is characterized by selectivity of action towards MCF-7 breast cancer and has low cytotoxicity towards normal cells. Considering the promising pharmacological potential of this compound and using spectroscopic techniques, HSA and human serum albumin nanoparticles (HSA-NP) were tested as carriers of this molecule. Based on the obtained data and the appropriate mathematical models (Stern-Volmer and Klotz models), it can be concluded that 10-Pyr-3,6-DAPT probably forms a weak (Ka = (5.24 ± 0.57) <semantics>×</semantics> 104 and Ka = (4.67 ± 0.59) <semantics>×</semantics> 104) for excitation wavelengths λex 275 nm and λex 295 nm, respectively) static complex (kq > 1010) with HSA (at Sudlow site II (subdomain IIIA), and the phenomenon of it having both strong therapeutic and toxic effects is possible. High encapsulation efficiency of 10-Pyr-3,6-DAPT into the HSA-NPs was obtained, and the changes in albumin secondary structure due to the presence of 10-Pyr-3,6-DAPT were registered. Based on the data presented, it can be concluded that due to the high toxic effects of 10-Pyr-3,6-DAPT, a better carrier may be HSA-NPs.